Association of Hearing Impairment With Higher-Level Physical Functioning and Walking Endurance: Results From the Baltimore Longitudinal Study of Aging. (18th May 2021) - Martinez-Amezcua, Pablo; Kuo, Pei-Lun; Reed, Nicholas S; Simonsick, Eleanor M; Agrawal, Yuri; Lin, Frank R; Deal, Jennifer A; Ferrucci, Luigi; Schrack, Jennifer A
Abstract: Background: Although hearing impairment (HI) is linked to poorer physical functioning, the longitudinal associations between HI and higher-level functional measures are unclear. Method: Data are from the Baltimore Longitudinal Study of Aging (2012–2019). Using pure-tone audiometry, we categorized hearing into normal, mild, and moderate or greater HI. Physical function was assessed with the expanded Short Physical Performance Battery (eSPPB) and walking endurance with time to walk 400 m. Multivariable and mixed-effects linear models tested the hypotheses that participants with HI, at baseline, have poorer physical performance and walking endurance, and faster decline over time (up to 6 measurements). In a subset ( n = 526), we further adjusted for vestibular function. Among participants with HI, we evaluated the differences in eSPPB scores and walking endurance between hearing aid users and nonusers. Results: Of 831 participants, 26% had mild, and 17% moderate or greater HI. After adjustment for demographics and medical history, moderate or greater impairment versus normal hearing was associated with poorer function (0.17 [95% CI: 0.09, 0.26] lower eSPPB score, and 13.3 [95% CI: 3.31, 23.4] seconds slower 400-m walk time) and faster decline in these parameters over 6 years. Adjustment for vestibular function did not attenuate these associations. Hearing aid users walked 400 m 24 seconds faster than nonusers ( p = .001). Conclusion: Moderate or greater HI is associated with poorer initial and greater decline in higher-level physical performance. The observation that hearing aid users had better walking endurance suggests that screening for and treatment of HI may delay or slow progression of hearing-related functional decline.